Prevalence and risk factors associated with anti-Leptospira spp agglutinins in cattle from dairy farmers in Ji-Paraná, RO, Brazil - Rocha, W. B.; Schein, F. B.; Boas, R. Vilas; Assis, N. A. [UNESP]; Mathias, L. A. [UNESP]; Silva, G. C.P.; Ferreira, M. B.; Santos, M. D. (My University, 2022)
Leptospirosis affects several animal species, including man. This study aimed to evaluate the prevalence of Leptospira spp. and to identify factors associated with the risk of Leptospira spp. in dairy cattle in the municipality of Ji-Paraná, RO, Brazil, sampled by rural sector, from September 2012 to November 2013. Blood samples from 627 dairy cows were randomly collected from 63 farms belonging to six rural sectors. Leptospirosis was diagnosed by the microscopic serum agglutination technique. Of the 627 animals tested, 255 had anti-Leptospira antibodies (40.48%, 95% CI: 36.64-44.31) and 57 of the 63 studied dairy farms (90.5%, 95% CI: 83.23-97.72) had at least one reactive animal. The results indicate that serovar Hardjo had the highest (12.38%. 95% CI: 10.03-15.18) followed by serovars Shermani, Wolffi, Hebdomadis and Canicola occurrence in dairy cows. Additionally, infection was also associated with abortion occurrences in cows of 36 farms (57.14%) and the presence of dogs roaming free with access to pasture, water and cattle in 47 farms (74.60%). Therefore, free-roaming animals are considered a predisposing factor, highlighting the need for adopting prophylactic measures while raising the awareness from rural producers about the importance and the economic losses that leptospirosis may cause.
Keywords: Dairy cattle; Epidemiology; Hardjo; Leptospirosis